The Development of IBS Structure Panel Using Revit Software - Khairi Supar; Hisyamudin, Nur Atiqah Izzati; Abdullah, Muhammad Nurarif Amsyar Muhamad Amin; Amsyar Muhamad Amin Abdullah; Mohd Noor, Nurul Fatin Shazwani; Nur'Ain Idris; Hilton Ahmad (Multidisciplinary Applied Research and Innovation, 2024)
Autodesk’s Revit is a sophisticated Building Information Modelling (BIM) software that transforms the way architects, engineers, and construction professionals create, collaborate, and visualize their projects. Revit has become the industry standard for producing and maintaining complex building models due to its rich set of tools and capabilities. Revit, at its heart, allows users to generate sophisticated 3D models that span the whole building lifespan. These models function as a digital representation of the actual structure and include precise information about its components, materials, and systems. Unlike conventional 2D drawing software, Revit’s parametric modelling methodology allows for dynamic modifications to the model, updating all connected elements and views instantly. This not only speeds up the design process but also helps to reduce mistakes and inconsistencies. One of Revit’s primary benefits is its capacity to promote multidisciplinary cooperation. Revit provides a large range of tools and features that are specialized to certain professions. Architects may use Revit to construct precise floor plans, elevations, and sections, as well as explore numerous design possibilities and generate realistic representations and visualizations. Structural engineers may analyse and simulate the behaviour of building structures, assuring its stability and performance. MEP engineers may design and organize the complicated systems that assure a building’s operation, such as HVAC, electrical, and plumbing. Contractors may use the model to provide accurate quantity takeoffs and constructability studies, which aids in project estimation and planning. Furthermore, Revit facilitates the connection of various data sources and software program, allowing users to smoothly import and export information. This interoperability increases the software’s adaptability and integrates it into the broader project workflow.